Visible light-driven novel g-C3N4/NiFe-LDH composite photocatalyst with enhanced photocatalytic activity towards water oxidation and reduction reaction1. Issue 36 (28th September 2015) - Nayak, Susanginee; Mohapatra, Lagnamayee; Parida, Kulamani
<x xml:space="preserve">Abstract</x> Dispersion of exfoliated CN over the surface of exfoliated LDH composite materials, and its photocatalytic water splitting under visible-light irradiation.